Cultural tourism as counterculture within subcultures of mass culture - Mavrina, Hanna (Skhid, 2013)
The analysis of cultural tourism is given in the article as alternative cultural practice which counteracts unifying and levelling processes of mass culture. Priorities of cultural strategies of tourism are determined in the context of ethnic culture and national traditions.